Parameter estimation of fractional uncertain differential equations via Adams method - Wu, Guo-Cheng; Wei, Jia-Li; Luo, Cheng; Huang, Lan-Lan (Nonlinear Analysis: Modelling and Control, 2022)
Parameter estimation of uncertain differential equations becomes popular very recently. This paper suggests a new method based on fractional uncertain differential equations for the first time, which hold more parameter freedom degrees. The Adams numerical method and Adam algorithm are adopted for the optimization problems. The estimation results are compared to show a better forecast. Finally, the predictor–corrector method is adopted to solve the fractional uncertain differential equations. Numerical solutions are demonstrated with varied α-paths.